Virtual Assisted Self Interviewing (VASI): An Expansion of Survey Data Collection Methods to the Virtual Worlds by Means of VDCI - Mark W. Bell; Edward Castronova; Gert G. Wagner (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
Changes in communication technology have allowed for the expansion of data collection modes in survey research. The proliferation of the computer has allowed the creation of web and computer assisted auto-interview data collection modes. Virtual worlds are a new application of computer technology that once again expands the data collection modes by VASI (Virtual Assisted Self Interviewing). The Virtual Data Collection Interface (VDCI) developed at Indiana University in collaboration with the German Socio-Economic Panel Study (SOEP) allows survey researchers access to the population of virtual worlds in fully immersive Heads-up Display (HUD)-based survey instruments. This expansion needs careful consideration for its applicability to the researcher's question but offers a high level of data integrity and expanded survey availability and automation. Current open questions of the VASI method are an optimal sampling frame and sampling procedures within e. g. a virtual world like Second Life (SL). Further multi-modal studies are proposed to aid in evaluating the VDCI and placing it in context of other data collection modes.
Keywords: C81; C88; C93; Y8; 330; Interviewing mode; PAPI; CAPI; CASI; VASI; VDCI; second life; Online-Befragung; Virtuelle Realität; Social Web; Computerspiel; Internet